Standardization of the roasting process for peanuts - Garcia, Bernarda Manahan; Benedicto, Ana Marie Q. (2002., 2002)
ABSTRACT The current practice of roasting peanuts is a hit and miss method. The endpoint of roasting is based mainly on the color of the peanuts. The roasting process thus need to be standardized and this can be based on a more objectively defined parameters such as the determination of the roasted peanuts' moisture content, water activity and moisture sorption isotherm. Values obtained for the roasted peanuts' moisture content and water activity were 1.97% and 0.52 respectively. Constructed moisture sorption isotherm taken at 28°C was of a typical sigmoid shape. The calculated BET moolayer, taken as the safe minimum moisture level, was 0.90% and its critical moisture content as determined by a continuous sensory analysis was at 2.70%. The allowable water vapor transmission rate of packaging material was computed based on established critical and initial moisture levels.
Thesis (BSFT)--University of the Philippines Diliman.
Keywords: Peanuts